Photodegradation of cresols by ZnO and Mn-doped ZnO nanoparticles. - Abdollahi, Yadollah (2011)
Institute Of Advanced Technology Environmental pollution and particularly water pollution on a global scale has drawn the attention of scientists to the vital need for an environmentally clean and friendly chemical process. Photocatalytic oxidation, an advanced oxidation method, has proven reliability to eliminate persistent organic pollutants from water. Recently, interest in ZnO as a photocatalyst has increased but it has been mainly used under ultra violet (UV) irradiation. Since 46% of solar energy consists of visible light, and is more economical than UV light when used on a large scale, there has been much interest in modifying ZnO in order to apply it under visible irradiation. However, no study has been conducted on aquatic cresols photodegradation using commercial ZnO, synthesized ZnO (undoped), and Mn-doped ZnO under UV and visible irradiation. In this study, photodegradation of cresols was investigated using commercial ZnO.suspension under UV irradiation and visible light irradiation. The background of the study shows that cresols are stable under UV irradiation and visible light irradiation and about 7% of cresols are adsorbed over ZnO in the dark. The different variables studied include cresols concentration, photocatalyst dosage, and pH on the efficiency of photocatalytic degradation. In the optimum condition, photodegradation of cresols under UV irradiation is 100-ppm cresols at 2.5g/L ZnO, while under visible irradiation it is 25 ppm at 1.5g/L ZnO. Cresols photodegradation is favorable in pH range 6 to 9. In photodegradation of cresols, kinetics of photodegradation (R2≈0.99) is consistent with pseudo-zero order rate scheme. UPLC detected intermediates for o-cresol are 2-methylresorcinol, 2.5-hydroxybenzaldehyde and salicylaldehyde under UV irradiation and 2-methylresorcinol, 2.5-hydroxybenzaldehyde under visible light irradiation. For m-cresol, detected intermediates are 2.5-hydroxy-benzaldehyde, 3.5-hydroxytoluene and 3-hydroxy-benzaldehyde under UV irradiation, while 3.5-hydroxytoluene is detected as intermediate under visible light irradiation. The p-cresol detected intermediates are 4-hydroxy-benzaldehyde and methyl-4-hydroxybenzoate under UV irradiation, while only 4-hydroxy-benzaldehyde is detected in visible light irradiation. TOC studies indicate that 77% (o-cresol), 72% (m-cresol) and 85% (p-cresol) under UV irradiation, and 75% (o-cresol), 75% (m-cresol) and 85% (p-cresol) under visible light irradiation, of total organic carbon are exited from the solution during irradiation time. It was observed that photodegradation of cresols under UV is more effective than under visible light irradiation. To enhance hotodegradation of cresol under visible light, ZnO and Mn-doped ZnO (0-2.0% Mn) were synthesized by the co-precipitation method. The results of photocatalysts characterization show that 1%wt Mn-doped ZnO in comparison with undoped, 0.5%, 1.5% and 2% Mn-doped ZnO has higher surface area, lower particle size and lower agglomerate. Moreover, the calculated band gap of 1% Mn-doped ZnO is lower than others. The photocatalyst studies show that photodegradation efficiency and rate of reaction of undoped ZnO are comparable to orslightly better than commercial ZnO. The photocatalyst studies show that 1%wt Mndoped ZnO has maximum adsorption, %efficiency and rate of reaction. In conclusion,1%wt Mn-doped ZnO was selected as the best photocatalyst for removing cresols. The optimization of reaction condition illustrates that the maximum photodegraded cresolsconcentration is 35 ppm. The proper amount of photocatalyst is 1.5g/L and the maximum cresols photodegradation observed in pH 6-9. The detected intermediates are 2-methylresorcinol,2.5-hydroxybenzaldehyde and salicylaldehyde for o-cresol, 3.5-hydroxytoluene and 2.5-hydroxy-benzaldehyde for m-cresol, and 4-hydroxybenzaldehyde for p-cresol. TOC studies show that 70% (o-cresol), 68% (m-cresol) and 73% (p-cresol) of total organic carbon are exited from the solution during irradiation\ time. Reusability studies show that 1% wt Mn-doped ZnO can be used more than three times. The final conclusion is that 1% wt Mn-doped ZnO may enhance the photocatalyst activity of ZnO under visible light.